Dorothy Day: Love for One's Daughter and Love for the Poor - Yohe, Katherine M. (Horizons, 2004)
Because of how often Dorothy Day (1897-1980) was away, helping to co-found the Catholic Worker movement, her daughter Tamar nicknamed her, "Be-going." Others have called Dorothy a neglectful parent. This article provides an overview of Tamar's life, and for each period of Tamar's life it examines what Dorothy wrote during that time about motherhood and her relationship with her daughter. It seeks to clarify to what extent Dorothy's efforts to serve the poor led to a neglect of her daughter, and if there was any change in how she balanced these different relationships over the years. It also explores whether or not Dorothy understood and experienced motherhood as a holy and sanctifying vocation.